The Study of Paddy Dryer Using Basalt Stone As Heat Storage Media From Biomass Combustion - M Ridwan Dwi Astanto; Leopold Oscar Nelwan; Edy Hartulistiyoso (Jurnal Keteknikan Pertanian, 2022)
The objectives of this research were to study the characteristics of thermal storage basalt rock by using biomass combustion with respect to manual adjusted airflow, combustion rate and the gap distance between the storage base and the furnace base as well as to evaluate the performance of the heat storage system for paddy drying. The heat storage characteristics experiment was carried out in two stages, namely heat charging and discharging. The tests were carried out with two gap distances, namely 23 cm and 30 cm. In general, the closer distance (23 cm) gives better performance, where at the targeted outlet temperature of 40˚C, an average discharging time of 664 minutes and a discharging efficiency of 73.5% were obtained. At the targeted outlet temperature of 45˚C, an average discharging time of 452 minutes with an average discharging efficiency of 65.75% were obtained. Furthermore, the heat storage system was applied for paddy drying. The drying experiment was carried out twice, each using an average outlet air temperature of 45.5˚C and 41.4oC with an initial grain moisture content of 22.82 and 13.88 %w.b., respectively. Drying time of 360 minutes for the first experiment and 420 minutes for the second experiment with specific energy consumption of 5.45 MJ/kg evaporated water and 5.31 MJ/kg evaporated water, respectively were obtained. Even though it uses direct heating by using coconut shell combustion, this drying method did not affect the aroma of the rice produced.